Bacterial consortium for copper extraction from sulphide ore consisting mainly of chalcopyrite - Romo,E. (2013)
The mining industry is looking forward for bacterial consortia for economic extraction of copper from low-grade ores. The main objective was to determine an optimal bacterial consortium from several bacterial strains to obtain copper from the leach of chalcopyrite. The major native bacterial species involved in the bioleaching of sulphide ore (Acidithiobacillus ferrooxidans, Acidithiobacillus thiooxidans, Leptospirillum ferrooxidans and Leptospirillum ferriphilum) were isolated and the assays were performed with individual bacteria and in combination with At. thiooxidans. In conclusion, it was found that the consortium integrated by At. ferrooxidans and At. thiooxidans removed 70% of copper in 35 days from the selected ore, showing significant differences with the other consortia, which removed only 35% of copper in 35 days. To validate the assays was done an escalation in columns, where the bacterial consortium achieved a higher percentage of copper extraction regarding to control.